Strength Analysis of Planetary Gear Train of A New Shearer Cutting Unit - Zhao Lijuan; Qiao Meina; Lan Jinbao (Jixie chuandong)
Taking the planetary gear train in a new type of thin seam shearer cutting part as the research object,based on multi-body dynamics theory,the rigid-flexible coupled model of the shearer cutting part is established,and the dynamic simulation analysis is carried on,the stress and deformation of the planetary gear train parts are obtained.The structure improvement of the sun wheel and planet carrier is carried out,the maximum mesh stress on sun wheel tooth surface is decreased by423.26 MPa after improvement,the stress concentration phenomenon on planet carrier is basically eliminated,the fatigue life is improved to 8.302 2×107 times.The research methods provides a quantitative basis for the design of planetary gear train,reduces the development cost in the process of production,improves the benefit of enterprise.